A review of the Rett Syndrome Behaviour Questionnaire and its utilization in the assessment of symptoms associated with Rett syndrome - Percy, Alan K.; Neul, Jeffrey L.; Benke, Timothy A.; Marsh, Eric D.; Glaze, Daniel G. (Frontiers in Pediatrics, 2023)
based on 250-word limit; current 239) The Rett Syndrome Behaviour Questionnaire (RSBQ), which is completed by the caregiver, is one of the most widely used efficacy measures in clinical studies of Rett syndrome (RTT) due to its specificity to the core features of RTT. As healthcare providers participate in routine healthcare assessments of individuals with RTT in clinical practice, there is a need for these providers to understand the psychometric properties of the RSBQ and how it relates to the core clinical features of RTT. Here, we describe the characteristics of the RSBQ, review the literature on its validity and reliability as well as its performance in a phase 2 study and the recent phase 3 LAVENDER study. The RSBQ was first shown to discriminate RTT from other intellectual disorders with good inter-rater and test-retest reliability scores. It was subsequently validated as an appropriate instrument for measuring behavior in females with RTT and adopted as a clinical trial outcome. In LAVENDER, the FDA-approved drug trofinetide significantly improved the RSBQ total score over placebo in girls and women with RTT and change from baseline for all RSBQ subscores were directionally in favor of trofinetide. The change in RSBQ was aligned with the Clinical Global Impression-Improvement scale, suggesting that improvement in behavioral components may be related to overall clinical status. Given its validity and ubiquity in RTT clinical studies, it is important that the interplay of the domains and the psychometric profile of the RSBQ are understood.